SARS-CoV-2 vaccines and their challenges against the variants - Shrestha, Umid Kumar (Journal of Advances in Internal Medicine, 2021)
The coronavirus disease 2019 (COVID-19) pandemic has lead to the several researches for the development of the new severe acute respiratory syndrome corona virus 2 (SARS-CoV- 2) vaccines, namely mRNA vaccine, viral vector vaccine, recombinant protein vaccine and inactivated vaccine, with an objective to achieve the response which include production of neutralizing antibodies, generation of a T-cell response, and avoidance of immune-enhanced disease. Over a course of time, the SARS-CoV-2 virus has evolved and lead to mutations; the virus with one or more new mutations is referred to as a “variant” of the original virus. All new strains (P.1 from Brazil, B.1.351 from South Africa, B.1.1.7 from the UK and B.1.617 from India) have mutations in the spike protein, resulting in the threat to the effectiveness of the current available first generation vaccines. Hence, there might be the need of the development of the modified next generation of vaccines, which take care of all those variants. Nevertheless, the current first generation vaccines may still provide satisfying immunity against SARS-CoV-2 variants. Most vaccines are expected to provide protection against hospitalizations/deaths from these variants and a booster vaccine against these variants is likely to be effective. Hence, the current vaccination must proceed. As we are aware that the more the virus spreads, the more variants are likely to appear. In order to stop the spread of SARS-CoV-2 variants, it is important to get the vaccines once it is available and not to forget about the need to wash hands frequently, keep at least 1m distance from others and wear a mask. With the development of the effective SARS-CoV-2 vaccines and implementation of public health measures, we can surely defeat SARS-CoV-2 virus in COVID-19 battle and end this pandemic.